Novel aerosol extinction coefficients and lidar ratios over the ocean from CALIPSO–CloudSat: evaluation and global statistics - D. Painemal; M. Clayton; R. Ferrare; S. Burton; D. Josset; M. Vaughan (Atmospheric Measurement Techniques, 2019)
Aerosol extinction coefficients ( σ a ) and lidar ratios (LRs) are retrieved over the ocean from CALIPSO's Cloud-Aerosol Lidar with Orthogonal Polarization (CALIOP) attenuated backscatter profiles by solving the lidar equation constrained with aerosol optical depths (AODs) derived by applying the Synergized Optical Depth of Aerosols (SODA) algorithm to ocean surface returns measured by CALIOP and CloudSat's Cloud Profiling Radar. σ a and LR are retrieved for two independent scenarios that require somewhat different assumptions: (a) a single homogeneous atmospheric layer (1L) for which the LR is constant with height and (b) a vertically homogeneous layer with a constant LR overlying a marine boundary layer with a homogenous LR fixed at 25 sr (two-layer method, 2L). These new retrievals differ from the standard CALIPSO version 4.1 (V4) product, as the CALIOP–SODA method does not rely on an aerosol classification scheme to select LR. CALIOP–SODA σ a and LR are evaluated using airborne high-spectral-resolution lidar (HSRL) observations over the northwest Atlantic. CALIOP–SODA LR (1L and 2L) positively correlates with its HSRL counterpart (linear correlation coefficient r >0.67 ), with a negative bias smaller than 17.4 % and a good agreement for σ a ( r ≥ 0.78) with a small negative bias ( ≤|-9.2<mspace linebreak="nobreak" width="0.125em"/>%| <svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="57pt" height="13pt" class="svg-formula" dspmath="mathimg" md5hash="f67eeff144e6281595dbea33f3f700d0"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-12-2201-2019-ie00001.svg" width="57pt" height="13pt" src="amt-12-2201-2019-ie00001.png"/></svg:svg> ). ...